Production and Characterization of Nanoparticles from Citronella (Cymbopogon nardus) Extract Based on Chitosan Compounds - Damayanti, Alfa Dirsista; Rahmadhini, Noni; Kusuma, Ramadhani Mahendra (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Background: The use of nanoparticles in Indonesia has been developing and is now being applied across sectors, including agriculture, health, and industry. Nanoparticles derived from Cymbopogon nardus can be used as nanopesticides because they contain several compounds that suppress pathogen growth and reduce pest populations. Chitosan is an additional compound used in the fabrication of these nanoparticles. Methods: This research used materials and tools, including a PSA (Particle Size Analyzer), a SEM (Scanning Electron Microscope), Cymbopogon nardus, and chitosan. The research stages included extraction of Cymbopogon nardus, nanoparticle fabrication, PSA analysis, zeta potential measurement, and SEM observation. Results: The PSA test revealed that the Cymbopogon nardus nanoparticles had an average size of 907.2 nm. The zeta potential of the nanoparticles was –40.62 mV, indicating good electrostatic stability. SEM images showed that the nanoparticles had an irregular shape. Conclusions: The Cymbopogon nardus nanoparticles produced in this study, as characterized by PSA, zeta potential, and SEM analyses, demonstrated the expected characteristics of nanoparticles.